A combination of cecum microbiome and metabolome in CUMS depressed rats reveals the antidepressant mechanism of traditional Chinese medicines: A case study of Xiaoyaosan. (10th August 2021) - Lv, Meng; Wang, Yaze; Qu, Ping; Li, Shunyong; Yu, Zhiyi; Qin, Xuemei; Liu, Xiaojie
Abstract: Ethnopharmacological relevance: Xiaoyaosan (XYS), a representative and classic prescription in traditional Chinese medicines (TCMs), has been used for thousands of years for treating depression. The anti-depression effect of XYS has been demonstrated both clinically and experimentally. However, it is still unclear that whether XYS could regulate the abnormalities of gut microbiota and metabolites of cecum induced by depression, and in which way. This study aimed to explore the underlying mechanism of the anti-depressant effects of XYS from the perspective of cecal microbiota and metabolites. Materials and methods: Chronic unpredictable mild stress (CUMS)-induced depression-like rats were used as the depression animal model. Various classic behavioral tests were performed to assess the anti-depressant effects of XYS. Additionally, the composition, the richness, and the diversity of the cecum microbiota were assessed by 16S rRNA gene sequencing technology. Besides, the metabolic profiling of cecum samples was analyzed by 1 H-NMR metabolomics. Multivariate data analysis was then applied to screen the differential metabolites and to characterize the changes in cecum metabolites. Moreover, a correlation analysis between differential metabolites and crucial microbiota was conducted. Results: XYS significantly improved depressive behaviors and the abnormal diversity of cecum microbiota induced by CUMS. At the phylum level, XYS could significantly increase the abundance of Firmicutes while decrease the abundance of Actinobacteria in depressed rats. XYS significantly regulated the abundances of 9 out of 13 potential microbial biomarkers at the genus level. Cecal metabolomics showed that XYS could also regulate the abnormal levels of alanine, proline, lactate, and valine of depression rats. Conclusions: This study revealed, for the first time, from the perspectives of microbiota and cecum metabolites, the anti-depression mechanisms of XYS. This study is of significance for not only comprehensively understanding the anti-depression effects and mechanisms of XYS, but also for providing a research approach for revealing the underlying mechanisms of action of TCMs, i.e. to apply a combination of 16S rRNA gene sequencing and metabolomics. Graphical abstract: Image 1 Highlights: A combination of cecum microbiome and metabolome was used on CUMS depression rats. Both 16S rRNA gene sequencing and 1 H NMR based metabolomics were applied. XYS reversed the diversity and the composition of cecum microbiota of CUMS rats. Changes of cecal microbiota were correlated with potential metabolites regulated by XYS.